Multimodal Analysis of Pepsi Advertisement Video in Youtube - Kusumastuti, Ayutia; Pradipta, Bramantya (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This research explores multimodal analysis of Pepsi advertisements on YouTube and focuses on semiotic system based on Anstey and Bull's theory. This theory applied to three Pepsi advertisements using a qualitative descriptive method. The goal is to understand how the semiotic system in Pepsi advertisements conveys messages and builds a strong brand image. The research collected a total of 95 data points from the three advertisements. Linguistic analysis recorded 17 data points, visual analysis gathered 27 data points, audio analysis included 10 data, gestural analysis recorded 32 data points, spatial analysis included 9 data points. By combining these aspects together, this study provides an understanding of how Pepsi advertising conveys messages and builds a dynamic and modern brand image. Keywords: Advertisement, Discourse, Multimodal, Pepsi, Semiotic System.